2021
DOI: 10.1021/acs.joc.1c01440
|View full text |Cite
|
Sign up to set email alerts
|

Silver/ThioClickFerrophos-Catalyzed 1,3-Dipolar Cycloaddition and Tandem Addition–Elimination Reaction of Morita–Baylis–Hillman Adducts

Abstract: The asymmetric 1,3-dipolar cycloaddition of glycine imino esters to Morita−Baylis−Hillman (MBH) adducts or acetylated MBH adducts is described. The reaction was efficiently catalyzed by AgOAc/(R,S p )-ThioClickFerrophos at room temperature to afford pyrrolidine derivatives bearing a quaternary carbon as a single diastereomer with excellent enantioselectivity. When a cyclic pyrroline ester was used as the nucleophile instead of a glycine imino ester, the enantioselective tandem addition−elimination reaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The conjugated addition to arylidene malonate has been reported . Subsequently, we reported the asymmetric conjugate addition of 1-pyrroline-5-carboxylate to nitro alkenes, nitro isoxazoles, and Morita–Baylis–Hillman (MBH) adducts using our original chiral silver/ThioClickFerrophos (TCF) catalyst, and these reactions proceed with highly diastereo- and enantioselectively to afford corresponding conjugate adducts in good yields . Deng et al also reported the copper-catalyzed asymmetric conjugate addition of 1-pyrroline-5-carboxylate to nitro alkenes and nitroalkenyl indoles, demonstrating that products were converted to spiropyrrolidines and tropanes, respectively .…”
Section: Introductionmentioning
confidence: 92%
“…The conjugated addition to arylidene malonate has been reported . Subsequently, we reported the asymmetric conjugate addition of 1-pyrroline-5-carboxylate to nitro alkenes, nitro isoxazoles, and Morita–Baylis–Hillman (MBH) adducts using our original chiral silver/ThioClickFerrophos (TCF) catalyst, and these reactions proceed with highly diastereo- and enantioselectively to afford corresponding conjugate adducts in good yields . Deng et al also reported the copper-catalyzed asymmetric conjugate addition of 1-pyrroline-5-carboxylate to nitro alkenes and nitroalkenyl indoles, demonstrating that products were converted to spiropyrrolidines and tropanes, respectively .…”
Section: Introductionmentioning
confidence: 92%
“…In 2021, Kanemoto and Fukuzawa developed enantioselective domino Michael/Mannich reaction of glycine imino esters 191 with Morita−Baylis−Hillman adduct 213 promoted by 5 mol% of AgOAc combined with 5.5 mol% of chiral ferrocenyl‐based P,S‐ligand 214 (Scheme 58). [68] Carried out at room temperature in THF as solvent in the presence of TEA as base, the formal [3+2] cycloaddition afforded the corresponding chiral pyrrolidine derivatives 215 bearing a quaternary carbon stereocenter as single diastereomers with moderate to quantitative yields (50–98%) and good to excellent enantioselectivities (69–97% ee ). A variety of glycine imino esters bearing methoxy, methyl, fluoro, bromo, and trifluoromethyl groups on the phenyl ring at either ortho ‐, meta ‐, or para ‐positions were compatible, leading to the corresponding products with high ee values (≥89% ee ) excepted that exhibiting a methyl group at ortho ‐position (Ar= o ‐Tol) which reacted with a lower enantioselectivity (69% ee ).…”
Section: Enantioselective Silver‐catalyzed Domino Reactionsmentioning
confidence: 99%
“…In the same year, Kanemoto and Fukuzawa demonstrated that pyrroline esters 233 reacted with Morita−Baylis−Hillman adduct 234 through an enantioselective domino Michael/elimination reaction in the presence of a chiral silver catalyst in situ generated from 5 mol% of AgOAc and 5.5 mol% of chiral ferrocenyl‐based P,S‐ligand 214 [68] . As shown in Scheme 63, the one‐pot process performed in the presence of K 2 CO 3 as base resulted in the formation of the corresponding chiral exo ‐olefins 235 exhibiting a quaternary stereogenic center in moderate to quantitative yields (49–99%) and uniformly high enantioselectivities (83–98% ee ).…”
Section: Enantioselective Silver‐catalyzed Domino Reactionsmentioning
confidence: 99%
“…Kanemoto and Fukuzawa and co-workers developed the Ag-catalyzed [3 + 2] asymmetric endo-selective cycloaddition of Morita-Baylis-Hillman (MBH)-adducts 64 with imino esters 1 using AgOAc and ThioClickFerrophos ligand L16 to give the corresponding cycloadducts in 50-98 % yield with 69-98 % ees (Scheme 35). [43] The sterics and electronics of the imino ester had a significant impact on the levels of asymmetric induction observed. The reaction of cyclic imino ester required a slight modification of the reaction condition to provide a wide range of pyrroline esters via an enantioselective Michael addition À elimination process.…”
Section: Silvermentioning
confidence: 99%